The big short [videorecording (DVD)] - McKay, Adam, 1968-; Pitt, Brad, 1963-; Gosling, Ryan, 1980-; Bale, Christian, 1974-; Carell, Steve, 1962-; Tomei, Marisa; Lewis, Michael (Michael M.) (Paramount Home Entertainment, 2016)
The financial meltdown from the perspective of a number of players: Michael Burry, a bizarre autistic-like stock-picking genius, and the first to realize that the market's housing boom is based on a "house of cards" sham; Mark Baum, self-loathing fictional character whose firm picks up insider trading information from a wrong number phone call; Jared Vennet, a smart-aleck broker who confirms the ominous suspicion; and Charlie Gellar and Jamie Shipley, small-time players who hit it big.